Structural Adjustment, Industrialisation, and Export Promotion (The Pakistan Development Review, 1996)
The main objective of this paper was to explore if trade liberalisation has ushered in the large scale de-industrialisation that is feared by some to follow in its wake and whether it has been successful in enhancing export promotion. We relied on several different kinds of evidence to demonstrate that de-industrialisation has not coincided with the intensive structural adjustment period while export growth has. However, both industrialisation and export promotion in Pakistan have been below potential, below the mean for low income countries and have not even kept pace with progress in this regard in the low income country group. We were not able to establish, possibly due to the paucity of time-series observations, that either industry or exports generated positive externalities for or used resources more productively than the rest of the economy.